Pengaruh Positive Self Concept Sebagai Upaya Menumbuhkan Rasa Percaya Diri Atlet Bola Voli Pada Saat Bertanding - Ellyana Taskia; Dadan Mulyana; Bambang Erawan (Jurnal Kepelatihan Olahraga, 2022)
This study aims to determine whether the effect of Positive Self- Concept on the self-confidence of volleyball athletes when competing. The formation of a positive self-concept for athletes becomes something important. Positive Self-Concept directly affects one's self-esteem and feelings about oneself. Self-concept is an important part of a person's personal development. The method used is the experimental method. The research used in this research is the Pretest – Posttest Control Group Design. The population that the researcher used in this study was the female volleyball athlete Kharisma Premium. The total population to be studied is 18 senior athletes of Kharisma Premium volleyball. Samples were selected from the population using purposive sampling technique with a total of 12 people. The sample was given treatment in the form of Positive Self Concept which was arranged in an exercise program for 4 weeks. Before and after being given treatment, the sample was tested for self-confidence questionnaire. The results showed that there was a significant effect of Positive Self Concept in growing volleyball athletes' self- confidence when competing.